2007
DOI: 10.1007/s00011-007-6171-x
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial iNOS versus platelet iNOS: Responsibility for the platelet/leukocyte endothelial cell interaction in murine antigen induced arthritis in vivo

Abstract: The IVM data lead to an anti-inflammatory effect of NO, since NO followed an increase in platelet- and leukocyte- endothelial cell interaction in iNOS deficient mice with AiA. In addition, we have shown for the first time in vivo that platelet NO produced by iNOS seems to have a minor influence on the leukocyte induced tissue damage in contrast to endothelial iNOS. Therefore, selective platelet inhibition would not interfere with the protective effect of NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In antigen-induced arthritis (AiA) mouse, Andreas et al found that the development of AIA is related to the overexpression of iNOS in synovial microcirculation of knee joint, the elevated NO production and the increased leukocyte adhesion/infiltration in synovium (Veihelmann et al, 2001). Meantime, in the C57/Bl6 mice with AIA, the iNOS expresses, after stimulation, up to ten times more NO than the two constitutive forms of NOS (Schmitt-Sody et al, 2007). When detailed mechanisms are explored, researchers found that the activation of NF-κB in multiple arthritis models including RA, CIA and AIA is necessary for both the initiation and development of inflammation (Makarov, 2001).…”
Section: Nitric Oxide Synthase (Nos) and Nitric Oxide (No)mentioning
confidence: 99%
“…In antigen-induced arthritis (AiA) mouse, Andreas et al found that the development of AIA is related to the overexpression of iNOS in synovial microcirculation of knee joint, the elevated NO production and the increased leukocyte adhesion/infiltration in synovium (Veihelmann et al, 2001). Meantime, in the C57/Bl6 mice with AIA, the iNOS expresses, after stimulation, up to ten times more NO than the two constitutive forms of NOS (Schmitt-Sody et al, 2007). When detailed mechanisms are explored, researchers found that the activation of NF-κB in multiple arthritis models including RA, CIA and AIA is necessary for both the initiation and development of inflammation (Makarov, 2001).…”
Section: Nitric Oxide Synthase (Nos) and Nitric Oxide (No)mentioning
confidence: 99%
“…The model we used in our study has been used previously to evaluate anti-inflammatory effects (37)(38)(39)(40). Therefore, we concluded that this model would be the best choice for this research project.…”
Section: Discussionmentioning
confidence: 97%
“…Thrombotic inflammatory cells may have a role in this process. Besides monocytes, other cells may express iNOS, such as platelets and VSMCs (Schmitt‐Sody et al. 2007).…”
Section: Discussionmentioning
confidence: 99%